Typology of peach producers in Zacatecas, Mexico by attributes of fruit quality - Sánchez-Toledano, Blanca; Zegbe Domínguez, Jorge A.; Kallas, Zein (Revista Mexicana de Ciencias Agrícolas, 2019)
Zacatecas is positioned among the five leading peach producing states in Mexico. The peach is creole, yellow, bonded bone, firm pulp, sexually propagated and cultivated in temporary in ≈ 81% of the cultivated surface; what, highlights the low competitiveness of this crop. However, due to the number of producers dedicated to this crop, it enhances its socioeconomic importance in relation to other fruit trees. If it is intended to understand the characteristics and problems of the production units (UP) that serve as an instrument to optimize the allocation of public resources, and propose strategies that improve the development of agriculture, it is necessary to understand the heterogeneity of producers considering their socio-economic characteristics within the UP. Therefore, this research sought to analyze and segment technically and typologically the peach producers of the state of Zacatecas. The data was collected through a survey of 204 peach producers in Zacatecas, Mexico. The results suggest four types of producers: 1) those who plant peach without objective; 2) those who plant peach at the backyard level; 3) producers where the peach is part of an agricultural production system; and 4) peach business producers. In this last category, ≈ 31% of the producers were found, which could explain, in part, the low competitiveness of the crop with other product systems.
Keywords: Prunus persica (L.) Batsch.; competitiveness; socioeconomy